2011
DOI: 10.1029/2010je003656
|View full text |Cite
|
Sign up to set email alerts
|

Lunar swirls: Examining crustal magnetic anomalies and space weathering trends

Abstract: [1] We have used multispectral images from Clementine and data from Lunar Prospector's magnetometer to conduct a survey of lunar crustal magnetic anomalies, prominent lunar swirls, and lesser known swirl markings to provide new information on the nature of swirls and their association with magnetic anomalies. We find that all swirls and swirl-like albedo patterns are associated with areas of magnetized crust, but not all areas of magnetized crust are colocated with swirl-like albedo anomalies. All observed swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 90 publications
(264 reference statements)
4
101
0
Order By: Relevance
“…We cannot conclusively differentiate between these possibilities, but note that the velocity vectors of the reflected population appear to emanate directly from a region of strong crustal magnetic field, as shown in Figure 4 (lower right) (crustal field model from Purucker and Nicholas [2010]). This region, near the crater Firsov, contains albedo anomalies [Blewett et al, 2011]. These albedo features, typically associated with crustal magnetic fields, may indicate local shielding of the surface from space weathering, suggesting very strong localized reflection of the solar wind.…”
Section: 1002/2014gl061973mentioning
confidence: 99%
“…We cannot conclusively differentiate between these possibilities, but note that the velocity vectors of the reflected population appear to emanate directly from a region of strong crustal magnetic field, as shown in Figure 4 (lower right) (crustal field model from Purucker and Nicholas [2010]). This region, near the crater Firsov, contains albedo anomalies [Blewett et al, 2011]. These albedo features, typically associated with crustal magnetic fields, may indicate local shielding of the surface from space weathering, suggesting very strong localized reflection of the solar wind.…”
Section: 1002/2014gl061973mentioning
confidence: 99%
“…Previous near-infrared observations of lunar swirls show them to be optically immature compared with the surrounding terrains 10 . Space weathering leads to optical maturation of the surfaces of airless bodies and is thought to be caused by two main processes: (1) solar wind sputtering and/or implantation of hydrogen atoms, leading to the formation of nanophase metallic iron blebs and (2) micrometeoroid bombardment that leads to the formation of agglutinitic glass and a reduced vapourdeposited coating 11 .…”
mentioning
confidence: 99%
“…Several swirl formation mechanisms have been proposed, including (1) solar wind standoff due to the presence of local magnetic fields, preventing solar wind sputtering and implantation, nanophase iron formation, and the resulting surface darkening associated with space weathering 3 , (2) recent comet impacts or micrometeoroid swarms that scoured the lunar surface, leaving a fine-gained, unweathered material and possibly imparting a remnant magnetization [4][5][6] , and (3) electrostatic levitation and deposition of high-albedo, fine-grained, feldsparenriched dust 7 . The association of all swirls with magnetic field anomalies of varying strength [8][9][10] has driven the development of each of these hypotheses. In this work, we use the unique midinfrared data set from the Diviner Lunar Radiometer to distinguish between these hypotheses.…”
mentioning
confidence: 99%
“…Later, as Apollo missions discovered rocks magnetized from the lunar surface, they found that the lunar magnetic field was distributed locally on the surface (Pearce et al 1972;Collinson et al 1973). Lunar swirl areas with high albedo on the lunar surface, in particular, exhibit high magnetic field strength (Blewett et al 2011). Therefore, the precedent lunar magnetic investigation, the Lunar Prospector mission, gathered magnetic data above the Reiner Gamma swirl, shown in Fig.…”
Section: Introductionmentioning
confidence: 99%